1969
DOI: 10.1002/macp.1969.021280124
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of A‐B‐A type block copolymers of poly(ethylene oxide) and poly(α‐methyl styrene) from dilute solutions

Abstract: This paper was read a t the Annual Meeting of the Society of Fiber Science and Technology, Japan, held on 27th May, 1968. 252Crystallization of A-B-A Type Block Copolymers pros.) in quadratischen Plattchen kristallisieren, ahnlich denen der Polyathylenoxideinkristalle. Elektronenmikroskopische Aufnahmen dieser Kristalle zeigten, daB die Poly-arnethylstyrol-Ketten aus dem kristallinen Teil ausgeschlossen und wahrend der Kristallisation auf der Oberflache der Einkristalle abgeschieden werden. So bilden sich laog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Such systems were examined to shed light on confinement effects on polymer crystallization [37,38]. When crystallization of PE or PEO-containing block copolymers from dilute solution was studied, microscopic [33,34,39] and scattering [31,32] studies confirmed that the PE and PEO blocks formed square crystalline plates with thickness between w5 and w20 nm. Thus, observation of PM-PDMS-PM crystal plates here is not surprising but in agreement with prior reports.…”
Section: Crystal Platesmentioning
confidence: 90%
See 1 more Smart Citation
“…Such systems were examined to shed light on confinement effects on polymer crystallization [37,38]. When crystallization of PE or PEO-containing block copolymers from dilute solution was studied, microscopic [33,34,39] and scattering [31,32] studies confirmed that the PE and PEO blocks formed square crystalline plates with thickness between w5 and w20 nm. Thus, observation of PM-PDMS-PM crystal plates here is not surprising but in agreement with prior reports.…”
Section: Crystal Platesmentioning
confidence: 90%
“…It was for potential discovery of new morphologies we initiated the study of aggregates of polymethylene-blockpoly(dimethyl siloxane)-block-polymethylene (PM-PDMS-PM) where the PM blocks are crystalline and are insoluble in most solvents at room temperature. While past studies on block copolymers containing crystalline polyethylene [31,32] (PE) or poly(ethylene oxide) [33,34] (PEO) block(s) have mostly dealt with large plate-like crystals with sizes >1 mm, we focus our attention here on PM nanodiscs covered by PDMS loops. We show that electron microscopy, which has been the most popular technique in establishing morphologies of block copolymer nanoaggregates and micelles, did beam damage to the nanodiscs, whereas tapping-mode AFM is effective in imaging these structures after the nanodiscs are aspirated on mica surfaces from toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have studied crystallizable block copolymers, but they have focused primarily on B−A−B triblock copolymers with the B block being the crystallizable block. Kawai et al studied B−A−B triblocks consisting of PEO and poly(α-methylstyrene) and observed the formation of thin platelet structures although the domains were not as sharply defined as in the diblock case . Dröscher and Smith used transient electric birefringence to study the kinetics of formation of square platelets of B−A−B triblocks consisting of PEO and poly(propylene oxide) …”
Section: Introductionmentioning
confidence: 99%
“…Kawai et al studied B-A-B triblocks consisting of PEO and poly(R-methylstyrene) and observed the formation of thin platelet structures although the domains were not as sharply defined as in the diblock case. 5 Dro ¨scher and Smith used transient electric birefringence to study the kinetics of formation of square platelets of B-A-B triblocks consisting of PEO and poly(propylene oxide). 6 They found that the platelet thickness is monodisperse after the final structure is formed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Thus, in opposite to amorphous diblock copolymers in a selective solvent that form mostly spherical micelles, semicrystalline diblock copolymers self-assemble to form crystalline lamellar domains in which the micellar core is covered by a layer of the solvated amorphous amorphous block. [2,[5][6][7][8][9] Up to now, platelets, spherical and cylindrical micelles are the morphologies observed in highly selective solvents where the insoluble block can crystallize. [2,3,6,8,[10][11][12][13][14] We present a morphological study of the micellization of an asymmetric semicrystalline block copolymer, poly(butadiene)-block-poly(ethylene oxide), in the selective solvent n-heptane.…”
Section: Introductionmentioning
confidence: 99%